1989
DOI: 10.1093/oxfordjournals.aje.a115168
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight, Skin Sensitivity, and Senile Cataract

Abstract: This study explores the association between sunlight exposure and senile cataract, taking into account such individual differences as skin sensitivity to sunlight and the use of sun-shielding devices, i.e., sunglasses and hats. A case-control study was conducted among 160 matched pairs of subjects between October 1, 1984 and June 1, 1985 at the University of Iowa Hospitals and Clinics in Iowa City, Iowa. Cases were selected from among all patients admitted for inpatient or outpatient cataract surgery who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Several population studies have documented a link between diabetes and senile cataract formation in persons aged 65 years and younger [21-26]. Conversely, a number of studies have shown little association of nuclear cataracts with diabetes [27-29]. Though this relationship continues to be debated, as are the underlying physiological mechanisms, premature opacification may occur due to an increased susceptibility to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several population studies have documented a link between diabetes and senile cataract formation in persons aged 65 years and younger [21-26]. Conversely, a number of studies have shown little association of nuclear cataracts with diabetes [27-29]. Though this relationship continues to be debated, as are the underlying physiological mechanisms, premature opacification may occur due to an increased susceptibility to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies have determines that the amount of sun exposure is directly correlated with incidence and prevalence of cataracts in the population [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Opacification of the crystalline lens that causes reduced passage of light is called a cataract.…”
Section: Cataractmentioning
confidence: 99%
“…On the same note the greater prevalence of cortical opacities in the lower nasal quadrant of the lens also provides indirect support to a possible role of sunlight in cataract etiology [14]. Other studies however reported negative or inconclusive results [15, 16, 17, 18]. These results may be explained, at least in part, by the high percentage of nuclear cataracts in the corresponding study samples, by different ranges of sunlight exposure among participants, by a different population mobility during lifetime or by residual confounding.…”
Section: Epidemiological Evidence:observational and Intervention Studiesmentioning
confidence: 99%